The World Is Not Small for Everyone: Inequity in Searching for Knowledge in Organizations - Singh, Jasjit; Hansen, Morten T.; Podolny, Joel M. (Management Science, 2010)
We explore why some employees may be at a disadvantage in searching for information in organizations. The “small-world” argument in social network theory emphasizes that people are, on average, only a few connections away from the information they seek. However, we argue that such a network structure does not benefit everyone: some employees may have longer search paths in locating knowledge in an organization—their world may be large. We theorize that this disadvantage is the result of more than just an inferior network position. Instead, two mechanisms—periphery status and homophily—jointly operate to aggravate the inefficiency of search for knowledge. Employees who belong to the periphery of an organization because of their minority gender status, lower tenure, or poor connectedness have limited awareness of who knows what and a lower ability to seek help from others best suited to guide the search. When they start a search chain, they are likely to engage in homophilous search by contacting colleagues like themselves, thus contacting others who also belong to the periphery. To search effectively, employees on the periphery need to engage in heterophilous search behaviors by crossing social boundaries. We find support for these arguments in a network field experiment consisting of 381 unfolding search chains in a large multinational professional services firm. The framework helps explain employees' unequal access to the knowledge they seek, a poorly understood yet important type of organizational inequity in an information economy.